An Average Model of DC–DC Step-Up Converter Considering Switching Losses and Parasitic Elements - Marco Faifer (MDPI AG, 2021)
Power electronic converters represent a pillar of modern power systems, especially since generation from renewable energy sources, such as photovoltaics, have been introduced. One of their main characteristics consists of the high flexibility in converting different voltage levels and waveforms. As for all the conversion devices, they are subjected to unavoidable losses introduced by non-ideal components. For this reason, in the last few decades numerous research activities have been devoted to model their behavior and predicting the global efficiency. In spite of the number of scientific publications on the topic, the non-idealities have been rarely studied in terms of their impact on the input-output characteristics of the converter. In this paper, the conventional equivalent circuit of a step-up DC/DC converter has been upgraded in order to introduce the effects of both conduction and switching losses. The obtained formulation, applicable to all DC/DC converters, allows a more accurate average model that is particularly suitable for the study of multi-converter architectures, as for the most recent renewable energy sources applications. Finally, thanks to a dedicated test setup, the results of an experimental campaign demonstrate how the new formulation faithfully predicts its electrical behavior.